Experimental Characterization and Energy Performances of Multiple Glazing Units with Integrated Shading Devices. (May 2017) - Zinzi, Michele; Ruggeri, Paolo; Peron, Fabio; Carnielo, Emiliano; Righi, Alessandro
Abstract: Modern architecture is characterized by the use of large glazed surfaces. New technologies ensure thermal insulation by multiple glazing units so that, maintaining good solar gains, highly glazed buildings can achieve good energy performance during the heating season. More complicated is the management of the energy performance during the cooling season due to high permeability to solar radiation. External shading devices are a suitable solution but they are often neglected for functional and aesthetic reasons. Solar protection devices can be, however, introduced in the air gap of multiple glazing units, providing solar protection without interfering with the building envelope. Solar and thermal properties of several solution of glazing units with in-gap shading devices were measured with advanced experimental set-up, to be compared with conventional systems. Numerical analyses were also performed to estimate the impact of this technology on the energy performance of office buildings.